Determinants of survival in extremely preterm infants born at 22–23 weeks: a retrospective cohort study - Kurimoto, Tomonori; Tokuhisa, Takuya; Kibe, Masaya; Ohashi, Hiroshi; Hirakawa, Eiji; Maeda, Takatsugu; Kamitomo, Masato (Frontiers in Pediatrics, 2025)
BackgroundThis study investigated the risk factors associated with mortality in infants born at 22–23 weeks and assessed the impact of different variables on survival outcomes.MethodsThis retrospective study included 185 infants born at 22–23 weeks at a single tertiary care center (2006–2023). Univariate and logistic regression analyses identified independent predictors of mortality.ResultsAmong 185 infants, 64 (34.6%) did not survive. Mortality was associated with a lower birth weight (509 g vs. 564 g, p = 0.0001) and higher rates of small for gestational age (SGA; 21.9% vs. 7.4%, p = 0.009). Independent predictors included SGA [odds ratio (OR): 5.8], tension pneumothorax (OR: 9.9), severe intraventricular hemorrhage (OR: 3.3), focal intestinal perforation (OR: 4.1), necrotizing enterocolitis (OR: 18.9), and early-onset sepsis (OR: 9.7). Cesarean delivery was associated with reduced mortality (OR: 0.3).ConclusionsTargeted management of these risk factors and cesarean delivery may improve the outcomes in this population.